2019
DOI: 10.1111/jan.14155
|View full text |Cite
|
Sign up to set email alerts
|

The influence of welfare state factors on nursing professionalization and nursing human resources: A time‐series cross‐sectional analysis, 2000–2015

Abstract: Aim The aim of this study was to examine the relationship between welfare states and nursing professionalization indicators. Design We used a time‐series, cross‐sectional design. The analysis covered 16 years and 22 countries: Australia, Austria, Belgium, Canada, Denmark, Finland, France, Germany, Greece, Ireland, Italy, Japan, Netherlands, New Zealand, Norway, Portugal, South Korea, Spain, Sweden, Switzerland, United Kingdom, and the United States, allocated to five welfare state regimes: Social Democratic, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…There is evidence of numerous links between the characteristics of welfare state regimes and the regulation of nurse and nursing professionalization, suggesting that the political context has to be acknowledged and addressed to significantly influence nursing employment and working conditions and health policy [ 86 , 87 ]. In addition, the presence of a Government Chief Nursing Officer (GCNO) position and the existence of a nursing leadership programme to effectively take action in government actions, are associated with a stronger regulation of employment and working conditions for nurses and regulation of nursing education [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence of numerous links between the characteristics of welfare state regimes and the regulation of nurse and nursing professionalization, suggesting that the political context has to be acknowledged and addressed to significantly influence nursing employment and working conditions and health policy [ 86 , 87 ]. In addition, the presence of a Government Chief Nursing Officer (GCNO) position and the existence of a nursing leadership programme to effectively take action in government actions, are associated with a stronger regulation of employment and working conditions for nurses and regulation of nursing education [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to report trends of the nurse workforce on a large scale, national level and over the past 15 years of period. As in many ways, the nursing human resources and education, and health and family policy all impact each other, 21 the results of the analysis in this article can be used for policy-making, The number of Chinese nurse workforce in 2017 (3.8 million) accounted for 18% of the nurse workforce in the world (20.7 million), and this number increased to 4.1 million in 2018. 22 The Chinese nurses per 1000 population were 2.94 in 2018, exceeding the minimum standard set by WHO (2 nurses per 1000 populations) and some developing countries (eg, India and South Africa), yet this density is still relatively below the average density of Organisation for Economic Co-operation and Development member countries (9 nurses per 1000 populations and 50% of WHO Member States in 2017).…”
Section: Discussionmentioning
confidence: 98%
“…To the best of our knowledge, this is the first study to report trends of the nurse workforce on a large scale, national level and over the past 15 years of period. As in many ways, the nursing human resources and education, and health and family policy all impact each other, 21 the results of the analysis in this article can be used for policy-making, healthcare administration, education and further research to strengthen nurse workforce.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, structural indicators include three secondary indicators: organization and personnel, training and education, medical materials and equipment. A large number of studies have shown that the allocation of nursing human resources has a direct impact on nursing outcomes (Gunn et al., 2019 ; Han et al., 2018 ). Therefore, the nurse–patient ratio and the bed‐nurse ratio become important sensitive indicators.…”
Section: Discussionmentioning
confidence: 99%